Methods of using carnosinol and analogs thereof - Anderson, Ethan; Katunga, Lalage; Aldini, Giancarlo (My University, 2015)
Embodiments of the present invention relate to methods of preventing or treating diabetes, an obesity/diabetes-related condition, insulin sensitivity, heart disease, mitochondrial dysfunction or liver disease comprising administering carnosinol or an analog thereof to a subject in need thereof.